A Bearing Capacity of Bamboo Cluster Pile on Saturated Soft SoilBased on the Direct load Test and CPT’S Data - Widodo, Bambang; Pratikso,; Rohim, Abdul (International Journal of Sustainable Construction Engineering and Technology, 2022)
Abstract: One of the constructions that can be used to overcome the problem of soft soil is pile mattress bamboo construction. This construction consists of bamboo arranged as mattresses and bamboo arranged as cluster piles. The cluster pile consists of several bamboo culms tied together (cluster pile).  Cluster pile capabilities that are not analyzed for strength can result in wastage or construction failure. The purpose of this study was to analyze the ability of clusters pile from direct observation and compare them based on sonder (CPT) data. The method is carried out by direct observation of the model at the research site. The model observed are clusters with a length of 8 m, inserted into soft soil and then vertical loading is carried out until the soil that supports it collapses. There are 3 types of clusters pile, namely cluster piles C3, C4, and C7. The results showed that the ultimate bearing capacity of the cluster based on the direct load test was relatively the same as the calculated with sonder data. The ultimate bearing capacity (Pult) can be determined by the equation, Pult = 7.4056.Ac, where Pult in (kg), and Ac is cluster area in (cm2).